2000
DOI: 10.1021/ja993204s
|View full text |Cite
|
Sign up to set email alerts
|

First 17O NMR Observation of Coordinated Water on Both Isomers of [Eu(DOTAM)(H2O)]3+:  A Direct Access to Water Exchange and its Role in the Isomerization1

Abstract: A complete mechanistic study of the solution dynamics of [Eu(DOTAM)(H 2 O)] 3+ is performed through 1 H and 17 O NMR variable pressure and temperature studies. An unambiguous understanding of the water exchange was possible thanks to the first 17 O NMR observation of the bound water signal on both the M-and m-isomers (M:). The water exchange on m is about 50 times faster than on M, and even though the equilibrium constant K ) [M]/[m] equals 4.5, the contribution of m to the overall exchange rate is 90%. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
175
3

Year Published

2001
2001
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 161 publications
(190 citation statements)
references
References 27 publications
12
175
3
Order By: Relevance
“…This difference is smaller than that observed by Dunand et al [13] for the more slowly exchanging [Eu(dotam)] 3+ ) isomers (dotam = 1,4,7,10-tetrakis(carbamoylmethyl)-1,4,7,10-tetraazacyclododecane). However, the two complexes [Gd(S-RRRR-1)]…”
Section: )]contrasting
confidence: 60%
See 1 more Smart Citation
“…This difference is smaller than that observed by Dunand et al [13] for the more slowly exchanging [Eu(dotam)] 3+ ) isomers (dotam = 1,4,7,10-tetrakis(carbamoylmethyl)-1,4,7,10-tetraazacyclododecane). However, the two complexes [Gd(S-RRRR-1)]…”
Section: )]contrasting
confidence: 60%
“…[9] Recent studies have suggested that the rate of water exchange in the two enantiomeric coordination isomers may differ by as much as two orders of magnitude. [10][11][12][13] The t M value measured for [Gd(dota)] À (244 ns) is a weighted average of the values for the coordination isomers present. [14] Although adequate for low-relaxivity agents, such a long average residence lifetime of water molecules is considered undesirable in the design of high-relaxivity contrast media.…”
mentioning
confidence: 99%
“…[43] The kinetics for the isomerization a . [44] This may be the result of the important structural changes required for the interconversion. Firstly, the two water±Gd III bonds, which are also stabilized by hydrogen bonds, must be successively broken, and, secondly, the torsion of the macrocyclic skeleton needs to recover a steady state.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest has been the nature of the two coordination isomers that exist naturally in a solution of LnDOTA. [1][2][3] Since the rate of water exchange is a critical parameter in contrast agent design 2 and one of the two coordination isomers of LnDOTA complexes exhibits substantially faster water exchange than the other, [4][5][6] understanding the physical characteristics of these two coordination isomers has been an important goal. Because they are in dynamic exchange in solution, the nature of each coordination isomer historically had to be deduced from measurements performed on mixtures of the two.…”
Section: Introductionmentioning
confidence: 99%